Computational interface for web-based access to dynamic contents. (9th August 2007) - Bhalla, Subhash; Hasegawa, Masaki; Gutierrez, Enrique; Berthouze, Nadia
Most information systems depend on a Database Management System (DBMS) to organise information. Access to such an information system is based on use of a database query language on the part of the user. This poses a skill level problem for medical staff at a hospital. As a result medical staff tend to depend on the database specialists, and programmers for access to information. To eliminate the complexities of a query language and to make a ubiquitous access a web-based information access system has been proposed for the end users. The test prototype is based on the notion of query-by-object. It allows a logical step-wise approach to access information resources. The proposed system allows a medical personnel pose queries at the same level as a trained database query language programmer.